The latest ‘southern protection system’ and the revived ‘fortress of Europe’ topos in Hungary - Kitanics Máté (Sciendo, 2021)
As a response to the processes of international migration in the Balkans, the Hungarian government in 2015 constructed a technical border defence system on the southern border of Hungary, also assigning manpower to guard the border. As a response to migration, this is not unique in Europe if we also consider previous and subsequent events. Although this topic has already been addressed by several authors from different perspectives, this paper is the first to analyse in detail the construction and characteristics of the technical border defence system, and the structure and operation of the assigned police and military forces. The paper also examines how government policy related to the protection of the southern border and the fence revived the ‘Hungary, the fortress/bastion of (Christian) Europe’ concept, and also how the Hungarian government communicated this in order to achieve its political objectives.